Framing the socialisation process of the DBA candidate: what can universities offer and what should candidates bring?. Issue 3 (1st September 2016) - Pervan, Simon; Blackman, Deborah; Sloan, Terry; Wallace, Michelle; Vocino, Andrea; Byrne, Cathy
ABSTRACT: In Australia, the Doctorate of Business Administration (DBA) remains a popular program but considerable anguish persists within the university sector over just what it is offering students. In this article, we use the process of postgraduate socialisation to understand how candidates, supervisors and administrators navigate pathways to successful completion and offering of a DBA program. We identify four modes of knowledge applicable to the DBA and suggest that universities and candidates may draw on one another's cultural capital to determine which mode(s) can be offered. We also illustrate how candidates exercise agency through their cultural and social capital as they move through the program. We present a conceptual framework to help guide future research, and resource allocation on the DBA.